Performance of CO2 Foam Huff and Puff in Tight Oil Reservoirs - Shabib-Asl, Abdolmohsen; Chen, Shengnan (Nancy); Zheng, Sixu (Frontiers in Energy Research, 2022)
The challenges associated with unconventional reservoirs are related to their intrinsic nature: extremely low porosity and permeability. Combination of horizontal wells and multistage hydraulic fracturing techniques have been developed to overcome the production obstacles and unlock the vast amount of oil in place in such formations. However, oil production still exhibits a sharp decline within the first 2 years after the stimulation, leading to an oil recovery of less than 15%. Thus, enhanced oil recovery methods need to be investigated to further increase the production rates and the recovery. In this study, laboratory experiments and numerical simulations were conducted to evaluate the performance of CO2 foam huff and puff process and its impacts on oil recovery in the tight oil formations. More specifically, the foam half-life was measured as a function of surfactant concentration and followed by the foam drainage ratio and its rheological properties in the subsequent tests. Reservoir simulations were conducted using the lab data and the field data collected from Cardium formation. Sensitivity analyses were finally carried out to investigate the effects of controlling variables on the CO2 foam performance. Experimental results revealed that the optimal surfactant concentration was found to be 0.2%, which is critical micelle concentration (CMC) point. Simulation results show that CO2 foam huff and puff can increase the oil recovery by more than 11% compared to that of the primary production. Moreover, Sensitivity analyses show that the production time, injection time, and soaking time are the main effecting parameters, while the injection rate and the incremental injection rate are less important.